1.2.1 Variance of A Random Variable Definition 1.19
1.2.1 Variance of A Random Variable Definition 1.19
1.2.1 Variance of A Random Variable Definition 1.19
2 Lecture 2
1.2.1 Variance of a random variable
Denition 1.19. Let X be a r.v and we set = E(X). The variance is X is denoted by Var(X)
and
Var(X) := E((X )2 )
and the standard deviation of X is the square root of the variance.
Intuitively, the variance measures on average how much does the random variable deviate from
its expectation/mean.
Lemma 1.20. Given a random variable X then for any constant a, b R,
Var(X) = E((X )2 )
= E(X 2 X + 2 )
(by linearity) = E(X 2 ) 2E(X) + 2
= E(X 2 ) 2 .
2. From denition
5
We compute now E(X), by using integration by parts
E(X) = xex dx
0
= xex 0 + ex dx
0
=1
Therefore Var(X) = 2 1 = 1
We see that the variance is X is the second moment of X subtract the rst moment of X squared.
The moments of a random variable are very important objects and we shall introduce in the following
a method to obtain the moments of a random variable.
Denition 1.22. The moment generating function (mgf) of a r.v X is denoted by
MX (u) := E(euX )
and we say that the mgf of X exists if MX (u) is nite in some interval containing zero.
Remark 1.23. The moment generating function of X exists if there exists h > 0 such that the
MX (x) is nite for x [h, h].
Example 1.24. Let X be a r.v with density function fX (x) = ex for x > 0. Then the moment
generating function of X is
E(euX ) = eux ex dx
0
= e(u1)x dx
0
e(u1)x
=
u1 0
from which we see that
1
1u u<1
E(euX ) =
u1
1
from which we can say that the mfg of X exists, since we can take a take h = 2 and the mgf of X
is nite on the interval [ 12 , 12 ].
Lemma 1.25. Suppose the moment generating function of a r.v X exists then
(r) dr
E(X r ) = lim MX (u) =: lim MX (u)
u0 u0 du
Proof. As almost always, we give only the proof for the continuous case. I give only a sketch proof,
dr dr
lim MX (u) = lim eux fX (x) dx
u0 du u0 du R
r
dr
d ux
(by magic , we interchange du and dx ) = lim e fX (x) dx
u0 R du
= lim xr eux fX (x) dx
u0 R
= lim E(X r euX )
u0
(by some more magic ) = E( lim X r euX ) = E(X r )
u0